Agricultural Extention Paradigm Private Companies in Bandung Barat District - Sulandjari, Kuswarini; Kurnia, Ganjar; J. Sugarda, Tarya; Hapsari, Hepi (Jurnal Penyuluhan, 2020)
The purpose of this study is to examine the paradigm of organizing and technical agricultural counseling of private company. This is a qualitative research, and data were collected using interview, observation, document study and FGD techniques. Study documents include reading the standard operational procedures (SOP) counseling, counseling materials, invitations, vouchers, and coupons. Data were analyzed by reading the entire text of the interview transcription, summarizing and eliminating duplication, classifying, describing patterns, and themes. Marketing officers deal with farmer consumers using marketingtechniques and extension methods. Technically, the method of providing knowledge, involving stakeholders, and counseling private companies uses paradigms: persuasive-participatory (solicitation and deliberation), educative participatory (education and deliberation) through information services, consultation, guidance, guidance and assistance in accordance with farmers’ interests, using a professional approach, satisfying farmers, providing equality and democracy. The results showed that the paradigm of agricultural extension providers of private companies is oriented to get benefit from the sale of agricultural facilities, or marketing agricultural products.